Nostalgia for religious symbols in the poetry of the fourth and fifth centuries AH from the Abbasid era - Tharthar, Sarah Adnan; Idan, Ekhlas Muhammad (Al-Adab Journal, 2023)
Themes of nostalgia are considered a nature in the soul of the Arab poet, especially in the Abbasid era, for the nature of his environment and his life in the desert and the Arabian Peninsula. The themes of nostalgia and alienation were not limited to man and place only, but the poet in the Abbasid era transcended them by broadcasting his emotional passion and burning feelings to draw a picture of his imagination that expresses his sense of loss. And his sense of nostalgia for religious symbols, as the Abbasid poet longs for fasting, Mecca, Mina, and the pilgrimage to Mecca. Therefore, nostalgia for religious symbols was an instinct for the Arab poet in the Abbasid era, who was associated with his true Islamic religion and lofty principles. Therefore, the subject of our research was titled "Nostalgia for Religious Symbols in the Poetry of the Fourth and Fifth Hijri Centuries of the Abbasid Era" with the aim of determining the purpose of nostalgia for religious symbols in all their forms, whether they were nostalgia for the past. For the divine presence, fasting Ramadan, or Mecca, and the feelings of pilgrims, Mina and Arafat, in order to bring the Abbasid poets closer to God Almighty.